1999
DOI: 10.1038/sj.gene.6363634
|View full text |Cite
|
Sign up to set email alerts
|

The interferon gene cluster: a candidate region for MS predisposition?

Abstract: The clinical benefits of interferon (IFN) ␤ therapy in some multiple sclerosis (MS) patients are still unexplained, raising the question whether polymorphism within the IFNB gene itself would provide an explanation. Screening the IFNB gene by single strand conformation polymorphism (SSCP) analysis and sequencing, a single nucleotide polymorphism was identified. Both alleles were distributed with similar frequencies in MS patients and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…Overall, these results implicate for the first time genetic variation in the IFN gene cluster with Th2-mediated diseases, whereas prior studies of a limited number of IFN variants have reported associations with Th1-mediated diseases, MS 40 and sarcoidosis. 47 Although we cannot exclude the possibility that some of these associations are due to typed or untyped coding variation, we note that the coding variation in the Hutterites appears to be confined to one or a few haplotypes.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Overall, these results implicate for the first time genetic variation in the IFN gene cluster with Th2-mediated diseases, whereas prior studies of a limited number of IFN variants have reported associations with Th1-mediated diseases, MS 40 and sarcoidosis. 47 Although we cannot exclude the possibility that some of these associations are due to typed or untyped coding variation, we note that the coding variation in the Hutterites appears to be confined to one or a few haplotypes.…”
Section: Discussionmentioning
confidence: 48%
“…Four of the exonic polymorphisms were previously reported: Asp57frameshift (171insA) and Ile184Arg in IFNA17, Cys20Stop in IFNA10, and Tyr51Tyr (153 C-T) in IFNB1. 39,40 Four nsSNPs reported in dbSNP were not present in the Hutterite screening set. These included one each in IFNA1 (rs2230050; freq.…”
Section: Sequence Variation and Patterns Of Ldmentioning
confidence: 99%
“…All software used for this paper is available for downloading. 15 the phenotype frequency for IFNA1:07 was 6.3% (OR 12.41, P c o8 Â 10 À4 ). The combination TCRB-5/HLA-DRB1, which corresponds to TCRBV6S3*2 and HLA-DRB1*03, has been described previously.…”
Section: Ms Case -Control Studymentioning
confidence: 99%
“…Associations for the single alleles were reported previously. 14,15 ACs including this predisposing allele and a certain allele of another locus seem to be strongly associated with MS. However, the display of nOR (Figure 4c; single-count model) shows that most of these associations can be explained by the individual effect of the IFNA-1:07 allele.…”
Section: Simulation Studymentioning
confidence: 99%
“…Research in the German population excluded the IFN-␤ gene as a candidate for MS predisposition, but suggested the existence of predisposing IFN-␣ genes. 23,24 Furthermore, the family of interferon regulatory factors constitutes clearly a very interesting target for future studies, as some of its members are located within or near chromosomal regions exhibiting significant linkage to MS. To these belong IRF2 at 4q35.1, IRF3 at 19q13.3-13.4 and IRF4 at 6p23-25. Among these, the IRF2 locus in particular is worth further study, since enhanced expression of IRF-2 in acute MS lesions as compared to normal white matter was recently uncovered by means of cDNA microarray technology.…”
mentioning
confidence: 99%